Emerging Methods for Efficient and Extensive Incorporation of Non-canonical Amino Acids Using Cell-Free Systems - Wu, Yang; Wang, Zhaoguan; Qiao, Xin; Li, Jiaojiao; Shu, Xiangrong; Qi, Hao (Frontiers in Bioengineering and Biotechnology, 2020)
Cell-free protein synthesis (CFPS) has emerged as a novel protein expression platform. Especially the incorporation of non-canonical amino acids (ncAAs) has led to the development of numerous flexible methods for efficient and extensive expression of artificial proteins. Approaches were developed to eliminate the endogenous competition for ncAAs and engineer translation factors, which significantly enhanced the incorporation efficiency. Furthermore, in vitro aminoacylation methods can be conveniently combined with cell-free systems, extensively expanding the available ncAAs with novel and unique moieties. In this review, we summarize the recent progresses on the efficient and extensive incorporation of ncAAs by different strategies based on the elimination of competition by endogenous factors, translation factors engineering and extensive incorporation of novel ncAAs coupled with in vitro aminoacylation methods in CFPS. We also aim to offer new ideas to researchers working on ncAA incorporation techniques in CFPS and applications in various emerging fields.